Exploring Teacher and Parent Perspectives on School-Based Masculinities in Relation to Mental Health Promotion - Wilson, Michael J.; Gwyther, Kate; Simmons, Magenta; Swann, Ray; Oliffe, John L.; Casey, Kate; Rice, Simon M. (Frontiers in Psychology, 2022)
The capacity for boys’ and young men’s mental health promotion to act via shifting masculine norms that are linked to poor mental health outcomes, highlights the need to improve the extent to which school-based programs can promote mental health through leveraging more positive embodiments of masculinity. To-date, the perspectives of parents and teachers on such processes are understudied. This qualitative study presents teacher and parent views regarding adolescent masculinities and avenues for school-based developmental programming for boys and young men. In this study, 16 individual qualitative interviews were undertaken with 10 parents (six females, four males) and six teachers (three females, three males), recruited from an independent all-boys’ grammar school in Melbourne, Australia. Thematic analysis of parents’ and teachers’ perspectives indicated their perception of the role of context-dependent ‘public’ and ‘private’ masculinities, the influence of Australian masculinity norms, and the role of private boys’ school cultures in the development of adolescent masculinities. Additionally, strategies for development encompassed participants’ appetite for boys’ exposure to positive role models, in addition to consistent and relevant developmental programming to support positive masculinity development. Findings have implications for efforts to support prosocial masculine identity development via school-based initiatives, as an avenue to promoting mental health of boys and young men.